ChemInform Abstract: AMVN‐Initiated Expedient Synthesis of Biaryls by the Coupling Reaction of Unactivated Arenes and Heteroarenes with Aryl Iodides. Issue 25 (24th June 2014) - Bhakuni, Bhagat Singh; Yadav, Abhimanyu; Kumar, Shailesh; Kumar, Sangit
Abstract 33 examples